(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
The results of three-year studies have established the influence of agricultural cultivation methods on the formation of productivity of sunflower hybrids and varieties. Problem statement. To increase the yield of sunflower, it is necessary to use modern scientifically based technologies for its cultivation, which are primarily based on the introduction of high-yielding hybrids and varieties, scientifically based application of mineral fertilizers and growth regulators. It is especially important to provide plants with additional nutrition with macro- and microelements when growing high-yielding hybrids and varieties with high genetic potential. The aim of the research was to establish the features of the formation of productivity of sunflower hybrids and varieties under the influence of mineral fertilizers and plant growth regulators in the conditions of the Southern Steppe of Ukraine. Research methods. The experiment was conducted in 2011–2013 on the experimental field of the Institute of Oilseed Crops of Zaporizhia district of Zaporizhia region. To solve the tasks set, a two-factor field experiment was established. Factor A – application of mineral fertilizers (4 options). Factor B – hybrid, variety (4 options). Factor C – application of growth regulators (5 options). The total number of options in the experiment – 80. Repetition – three times. The experiment design and accounting, measurements, and accompanying observations were carried out according to the methods of field experiments. Research results. When growing sunflower with the use of mineral fertilizers, the indicators of the number of seeds and the mass of seeds from one basket increased by: 62–126 pcs. and 6.1–11.4 g in the Serpanok hybrid; 31–90 pcs. and 4.6–10.6 g in the Marshal hybrid; 21–100 pcs. and 3.9–10.7 g in the Agent hybrid; 21–65 pcs. and 4.3–10.0 g in the Camelot variety. Foliar feeding with growth regulators contributed to the increase in these indicators by: 23–111 pcs. and 1.5–6.5 g in the Serpanok hybrid; 13–82 pcs. and 1.1–5.6 g in the Marshal hybrid; 16–101 pcs. and 2.0–6.5 g in the Agent hybrid; 6–70 pcs. and 0.8–6.0 g in the Kamelot variety. With an increase in the dose of mineral fertilizers, the effectiveness of growth regulators decreases. Under the influence of mineral fertilizers, the mass of 1000 seeds increased relative to the control (without fertilizers) by: 2.0–3.9 g in the Serpanok hybrid; 2.1–4.3 g in the Marshal hybrid; 2.1–4.1 g in the Agent hybrid; 2.2–5.8 g in the Kamelot variety. The greatest increase in this indicator from fertilizers was noted in the Kamelot variety. The highest values of the mass of 1000 seeds for hybrids and the variety were obtained when mineral fertilizers were applied at a dose of N60P60K60. Under the influence of growth regulators, the mass of 1000 seeds, depending on the nutritional background, increased by: 0.3–0.9 g in the Serpanok hybrid; 0.2–0.9 g in the Marshal and Agent hybrids; 0.2–1.1 g in the Kamelot variety. The greatest increase in this indicator from growth regulators was also noted in the Kamelot variety. The greatest values of the number of seeds and the mass of seeds from one basket and the mass of 1000 seeds for hybrids and varieties were obtained with the use of growth regulators Fulvigrin Stimul in the phase of 3–4 and 6–8 pairs of leaves + Ceron in the phase of 8–10 pairs of leaves and Fulvital Plus in the phase of 3–4 and 6–8 pairs of leaves + Ceron in the phase of 8–10 pairs of leaves. The increase in yield from mineral fertilizers was: 0.28–0.54 t/ha in the Serpanok hybrid; 0.22–0.48 t/ha in the Marshal hybrid; 0.23–0.50 t/ha in the Agent hybrid and 0.18–0.41 t/ha in the Kamelot variety. Foliar fertilization with growth regulators contributed to an increase in yield by: 0.07–0.28 t/ha in the Serpanok hybrid; 0.06–0.25 t/ha in the Marshal hybrid; 0.08–0.28 t/ha in the Agent hybrid and 0.04–0.24 t/ha in the Camelot variety. Conclusions. Higher yield levels of sunflower hybrids Serpanok (3.66–3.69 t/ha) and Marshal (3.33–3.36 t/ha) were achieved by growing them against the background of mineral fertilizers in doses of N40P60, N60P90 and N60P60K60 with spraying of crops with growth regulators Fulvigrin Stimul in the phase of 3–4 and 6–8 pairs of leaves + Ceron in the phase of 8–10 pairs of leaves and Fulvital Plus in the phase of 3–4 and 6–8 pairs of leaves + Ceron in the phase of 8–10 pairs of leaves, and the Agent hybrid (3.56-3.59 t/ha) and the Camelot variety (3.08 and 3.11 t/ha) – against the background of mineral fertilizers in doses of N60P90 and N60P60K60 with spraying of crops growth regulators Fulvigrin Stimul in the phase of 3–4 and 6–8 pairs of leaves + Ceron in the phase of 8–10 pairs of leaves and Fulvital Plus in the phase of 3–4 and 6–8 pairs of leaves + Ceron in the phase of 8–10 pairs of leaves.